Validación del método analítico por cromatografía líquida de alta resolución (hplc) para la cuantificación de naproxeno sódico 275mg y paracetamol 300mg en tabletas recubiertas - Díaz Honores, Isabel Alejandra (2016)
The present report aims to present documented evidence, that produced results are reliable, consistent and reproducible under the conditions laid down; taking into account that the validation is an essential requirement for the implementation of the good practices of laboratory. He was the validation of the analytical method for chromatography liquid of high resolution for quantification of naproxen sodium 275 mg and acetaminophen 300 mg in recubiert tablets containing naproxen sodium and acetaminophen as actives principles. Evaluating parameters as: specificity (selectivity), linearity, precision, accuracy, and robustness.Defined working conditions, conducted the analysis for the evaluation of validation parameters and was demonstrated by the experimental design, the analytical methodology is linear because obtained a correlation coefficient r = 0.999 5 and 0,9998 for naproxen sodium and acetaminophen ; is accurate with a global recovery of 99,61 % y 100,03% for naproxen sodium and acetaminophen ; is selective because that was not evident interference of degraded products or the excipients in the analysis of the active principle, these parameters within the set range.So we conclude that the validated method is reliable, consistent and can be used in the analysis of routine provided